2008
DOI: 10.1111/j.1601-5223.1983.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchanges and structural chromosome aberrations in relation to smoking in 91 individuals

Abstract: Sister chromatid exchanges (SCE) and structural chromosome aberrations were analyzed in peripheral blood lymphocytes and correlated to smoking habits of 91 individuals. There was no difference between smokers and nonsmokers, neither as regards the frequency of SCE, nor for the frequency of structural chromosome aberrations in the total material. In a subgroup exposed to epoxy resins, though, a significantly elevated number of SCE among the smokers was noted. Conversely, smoking did not have any effect as regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…On the other hand, an increase in SCE induction and cell cycle delay and a diminution in mitotic index have been observed in workers that apply pesticide sprays who also smoke, compared with smokers that were not exposed to pesticides, indicating that smokers run a higher risk of genetic damage if also exposed to pesticides. 57 Similarly, other studies have reported significantly elevated SCE values among smokers exposed to occupational hazards compared similarly exposed non-smokers and/or to non-exposed smokers, for example smokers handling chemical solvents in various types of laboratories compared with non-smokers, 58 smokers working in contact with epoxy resins compared with non-smokers, 29 and smokers exposed to lead compared with non-exposed smokers. In the last group, metal-induced chromosomal damage results in a delay in blast transformation and consequently the majority of lymphocytes were still in first-division metaphase in cell cultures after 72 h. [59][60][61][62] An increase in SCE was also reported in smokers exposed to petroleum derivatives compared with non-exposed smokers.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…On the other hand, an increase in SCE induction and cell cycle delay and a diminution in mitotic index have been observed in workers that apply pesticide sprays who also smoke, compared with smokers that were not exposed to pesticides, indicating that smokers run a higher risk of genetic damage if also exposed to pesticides. 57 Similarly, other studies have reported significantly elevated SCE values among smokers exposed to occupational hazards compared similarly exposed non-smokers and/or to non-exposed smokers, for example smokers handling chemical solvents in various types of laboratories compared with non-smokers, 58 smokers working in contact with epoxy resins compared with non-smokers, 29 and smokers exposed to lead compared with non-exposed smokers. In the last group, metal-induced chromosomal damage results in a delay in blast transformation and consequently the majority of lymphocytes were still in first-division metaphase in cell cultures after 72 h. [59][60][61][62] An increase in SCE was also reported in smokers exposed to petroleum derivatives compared with non-exposed smokers.…”
Section: Discussionmentioning
confidence: 88%
“…Our finding for the smokers, where SCE could be determined, is in agreement with the reports of other authors, who did not find an elevated SCE frequency in smokers. [14][15][16]29,43 However, the majority of studies undertaken in the 1970's and 1980's reported a smoke-related increase in SCE frequency in smokers not exposed to other contaminants. 1,[8][9][10][11][12][13]17,19,31,32,[44][45][46][47][48][49][50][51][52][53][54] There were significant correlations between age and number of years the subject had been smoking, as well as between RI and nicotine and cotinine levels and between CPK (M1, M2 and M3) and nicotine and cotinine levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations